Board examination stress effect on diastolic function. Issue 3 (12th November 2018) - Geraiely, Babak; Tavoosi, Anahita; Sattarzadeh, Roya; Hassanbeigi, Hamidreza; Larry, Mehrdad
Abstract: Background: To this date, effects of mental stress on cardiac function have not been clearly investigated. Although hemodynamic and neuroendocrine adverse effects of daily mental stress on cardiovascular morbidity and mortality have been reported, its direct impact on diastolic function of the heart has not been previously studied. In this study, we aimed to assess the role of Board Exam anxiety on right and left ventricular diastolic function in medical residents. Methods: Forty medical residents prior to participation in the medical board exam were enrolled in our study. Right prior to as well as 2 month after the exam, all residents underwent trans‐thoracic Doppler echocardiography. Right ventricular systolic and diastolic functions and echocardiography indices were measured. Levels of anxiety were measured using Beck Anxiety Inventory Questionnaire before and after the exam. Pre exam and post exam results of study population as well as low and high anxiety groups were evaluated. Results: Early to late mitral inflow velocity (E/A ratio) in LV inflow increased after board exam ( P ‐value <.001). E/A ratio in RV inflow increased after board exam ( P ‐value: .002). Early mitral inflow to its annular velocity (E/E' ratio) in septal wall decreased after board exam ( P ‐value<.001). The change in E/E′ RV free wall did not reach statistical significance ( P = .57). Mitral annuls velocities measured by TDI in septal and lateral wall and also tricuspid annulus velocity increased after board exam ( P ‐value<.05). The comparison of these changes between the high‐stress and low‐stress groups of residents revealed significant differences. Comparison of changes of E/A ratio in the mitral and tricuspid inflow as well as the E/E' in the septum and free wall of the right ventricle before and after the Board Exam between high‐stress and low‐stress groups was not statistically significant, although there was a trend of more changes in high‐ stress group residents. Conclusion: This is the first report of comprehensive sequential assessment of left and right ventricular diastolic functions during and after a real subacute stress occasion. The finding of a decreased E/A and E′ in response to mental stress suggests that repetitive mental stress may induce diastolic dysfunction which is a mechanism of diastolic heart failure in individuals at risk.